Low-temperature benchtop-synthesis of all-inorganic perovskite nanowires. Issue 46 (21st November 2017) - Kostopoulou, A.; Sygletou, M.; Brintakis, K.; Lappas, A.; Stratakis, E.
Abstract : Ultra-thin and highly uniform CsPbBr3 nanowires over micron-size lengths and widths down to the quantum confinement regime have been fabricated via a facile, low-temperature precipitation-based method. This synthesis approach is the first of its kind that is carried out on the work-bench. The nanowires' photoluminescence is shown to improve over time. Abstract : A facile, low-temperature precipitation-based method is utilized for the synthesis of ultra-thin and highly uniform cesium lead bromide perovskite nanowires (NWs). The reactions facilitate the NWs' crystalline nature over micron-size lengths, while they impart tailored nanowire widths that range from the quantum confinement regime (∼7 nm) down to 2.6 nm. This colloidal synthesis approach is the first of its kind that is carried out on the work-bench, without demanding chemical synthesis equipment. Importantly, the NWs' photoluminescence is shown to improve over time, with no requirement for tedious post-synthesis surface treatment.